2014
DOI: 10.3389/fnagi.2014.00003
|View full text |Cite
|
Sign up to set email alerts
|

Exercise enhances memory consolidation in the aging brain

Abstract: Exercise has been shown to reduce age-related losses in cognitive function including learning and memory, but the mechanisms underlying this effect remain poorly understood. Memory formation occurs in stages that include an initial acquisition phase, an intermediate labile phase, and then a process of consolidation which leads to long-term memory formation. An effective way to examine the mechanism by which exercise improves memory is to introduce the intervention (exercise), post-acquisition, making it possib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
34
0
3

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(39 citation statements)
references
References 68 publications
1
34
0
3
Order By: Relevance
“…Many studies have recently reported robust effects of physical exercise in aged animals on hippocampal neurogenesis and hippocampal memory performance (Kim et al, 2010; Barrientos et al, 2011; Kohman et al, 2012; Speisman et al, 2013; Merkley et al, 2014; Snigdha et al, 2014). For example, one study showed that 12 weeks of voluntary wheel running reversed the aging-associated memory deficits in the hippocampal-dependent task of place recognition (Siette et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Many studies have recently reported robust effects of physical exercise in aged animals on hippocampal neurogenesis and hippocampal memory performance (Kim et al, 2010; Barrientos et al, 2011; Kohman et al, 2012; Speisman et al, 2013; Merkley et al, 2014; Snigdha et al, 2014). For example, one study showed that 12 weeks of voluntary wheel running reversed the aging-associated memory deficits in the hippocampal-dependent task of place recognition (Siette et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Individual variability of learning and memory can also have a confounding effect on results (Snigdha et al, 2014). In this study population, a significant effect was seen for the pretraining and the absolute trials on day 1 data.…”
Section: Discussionmentioning
confidence: 65%
“…Additionally, acute exercise post-learning improved memory recall of some training tasks in senior dogs (Snigdha et al, 2014). For this reason, we cannot exclude that an exercise component of the arousing playful activity intervention contributed to the improved training performance.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…Langlois F, et al описали улучшение ког-нитивной функции среди пациентов пожилого возра-ста на фоне трехмесячного курса физических трени-ровок [8]. В экспериментах показано, что физические аэробные упражнения способствуют снижению функционального дефицита, связанного с когнитив-ным старением, тем самым повышая устойчивость головного мозга к старению [9]. Известно, что влияние физических тренировок на больных с сердечно-сосудистой патологией носит многоплановый характер [10].…”
Section: уитни и фридмана)unclassified